The effect of the 808nm diode laser on wound healing (experimental study on rabbit skin) (Sebha University Conference Proceedings, 2025)
Laser therapy is widely used in the field of dermatology and especially the wound healing process. However, there is no high-intensity laser used for the same treatment. Hence an investigation was carried out to study the effect of high intensity diode laser on a wound. 808 nm lasers were used. operated at different doses between 0.11 to 0.51 W/cm2 at reaction times of 30 s, 60 s, and 120 s per session. Four New Zealand White rabbits were used, each rabbit was approximately two and a half to three months old and weighed 4-3 kg. Six full-thickness open wounds (meaning that the wound extended through all layers of the skin) with a diameter of 6 mm were created on the dorsal part of the rabbits using a sterile iron scalpel with a sterile iron scalpel. The rabbits were divided into two groups. One was a control group and the other a treatment group, while the rabbit's back was stimulated five times daily with a constant energy density of 5 J/cm2 corresponding to different energy densities, between 0.1 to 0.5 W/cm2 with different exposure times of 50 seconds, 25 seconds, 17 seconds, 1 second and 10 seconds, respectively. The wound contraction, tensile strength and histology of the wound healing process were examined well. The photostimulation effect is responsible for enhancing tensile strength and facilitating collagen production. The wound contraction rate in the laser treatment group was two times faster compared to the control group. The wound contraction was improved after being exposed to 0.1 W/cm2 with the corresponding exposure time of 50 s. Low-level laser therapy is able to promote wound healing by promoting epithelialization and collagen fiber synthesis. Overall, the irradiated groups were more advanced in terms of healing than the non-irradiated group. This suggests that the 808-nm laser,